2021
DOI: 10.1007/s12072-021-10194-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of liver fibrosis by transient elastography in young children with chronic hepatitis B virus infection

Abstract: Background This study aimed to compare the diagnostic accuracy of transient elastography (TE) and biopsy for the detection of liver fibrosis in children with chronic hepatitis B (CHB). Methods This single-center prospective study included 157 CHB children aged 0–6 years. All patients underwent liver stiffness measurement (LSM) by TE and liver biopsy, separated by an interval of less than 1 week. Results The LSM, asp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…TE outperformed any indirect measures concerning specificity, PPV, NPV, and overall accuracy correlated to advanced fibrosis [20]. In addition, the results disagreed with Xu et al (2021), who found that APRI did not provide additional advantages over TE for discriminating hepatic fibrosis stages (F ≥ 2 and F ≥ 3) in chronic HBV children [19]. Luo et al (2022) studied the assessment of liver fibrosis by TE and multi-parameters model in young children with chronic hepatitis B virus infection.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…TE outperformed any indirect measures concerning specificity, PPV, NPV, and overall accuracy correlated to advanced fibrosis [20]. In addition, the results disagreed with Xu et al (2021), who found that APRI did not provide additional advantages over TE for discriminating hepatic fibrosis stages (F ≥ 2 and F ≥ 3) in chronic HBV children [19]. Luo et al (2022) studied the assessment of liver fibrosis by TE and multi-parameters model in young children with chronic hepatitis B virus infection.…”
Section: Discussionmentioning
confidence: 56%
“…TE outperformed HA in predicting any degree of fibrosis[18]. Similarly, Xu et al (2021) assessed liver fibrosis by TE in 157 young children (0-6 years) with chronic HBV and found that APRI did not provide additional advantages over stiffness for determining hepatic fibrosis stages(F ≥ 2 and F ≥ 3) and concluded that TE was a promising technique for diagnosing advanced fibrosis in chronic HBV children aged 0-6 years[19]. Furthermore, Lee et al (2013) evaluated and compared the ability of HA and TE to predict advanced hepatic fibrosis in 128 patients (pediatrics and young adults) and stated that TE outperformed HA in predicting advanced fibrosis…”
mentioning
confidence: 99%
“…Chang P. E. and others found that the optimal cut-off for LSM diagnostic significant liver fibrosis (F ≥ 2) in adults was 9.0 kPa, whose sensitivity and specificity were 67.4% and 75.4%, respectively [ 18 ]. And a recent study found that the cut-off values (specificity,sensitivity) for significant fibrosis and advanced fibrosis were 5.6 kPa (75.7%, 67.4%), 6.9 kPa (91.5%, 81.3%) respectively in CHB children aged 0–6 years [ 6 ]. The research of Xu ZQ and colleagues showed that the value of LSM increased with age, as the cut-off values for significant liver fibrosis (F ≥ 2) and progressive liver fibrosis (F ≥ 3) in children under 12 years old were 5.8 and 7.0 kPa, respectively, and they were 6.6 and 8.0 kPa for children above 12 years old [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were also divided into 5 stages F0, F1, F2, F3, and F4 according to the Scheuer system on pathological staging.The serologic examinations were performed within two weeks after the LB. The sample size in our study was calculated by the formula as follow: Nsp = (Z 1-α/2 × √ se [1] × (1 − se )/0.1) 2 = (1.96 × √0.915 × (1–0.915)/0.1) 2 ≈ 30 [ 6 ].This study was approved by the Ethics Committee of Hunan Children’s Hospital (IRB No. HCHLL-2019004), and obtained the formal written informed consent from all the parents and guardians of the participating children.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation